A novel approach in the management of placenta accreta spectrum disorders: A single-center multidisciplinary surgical experience at Tu Du Hospital in Vietnam - Xuan Trang Thi Pham; Anh Dinh Bao Vuong; Lan Ngoc Vuong; Phuc Nhon Nguyen (Elsevier, 2023)
Objective: Placenta accreta spectrum disorders (PASD) are the leading cause which results in highly maternal mortality during pregnancy. Although hysterectomy has been the gold standard for PASD, the recent study along with our experience has been demonstrated that the association between uterine myometrial resection and transverse B-Lynch suture in conservative management might be effective in the appropriate patients, thus we hereby attempted to determine this issue. Materials and methods: A retrospective observational study enrolled 65 patients at Tu Du Hospital in Vietnam between January 2017 and December 2018. This study included all pregnant women above 28 weeks of gestational age, who had undergone cesarean delivery due to PASD diagnosed preoperatively by ultrasound or upon laparotomy. Additionally, all patients who desired uterine preservation underwent modified one-step conservative uterine surgery (MOSCUS), avoiding peripartum hysterectomy. Results: Overall, the rate of successful preservation was 93.8%. Other main outcomes such as average operative blood loss was 987 mL, mean blood transfusion was 831 ± 672 mL; mean operative time was 135 ± 31 min and average postoperative time was 5.79 days. Postoperative complications included six out of 65 cases due to intraoperative bleeding and postoperative infection, requiring hysterectomy in 4 patients. Conclusion: MOSCUS was associated with less operative blood loss and blood transfusion amount. Its success rate of uterine preservation was approximately 94% in our study. Thus, this method can be acceptable in PASD management at our maternity health care center. Further studies might be necessary to evaluate the long-term effects of this method in PASD management.